CURRENT STATUS OF GRAPHIC TEACHING METHODOLOGY AND WAYS TO IMPROVE IT - Tanjarova Rano Akramovna; Elchiboyev Kamoliddin (Journals Park Publishing, 2024)
This article discusses the current state of teaching graphics and ways to improve it. Based on technological data and written sources, the author explores the specifics of the topic that have clarified the problem based on the available scientific literature.
Keywords: Computer graphics, education system, teaching methods, development.